Synthesis of Cucurbit[6]uril Using 1-Hydroxyethylidene-1,1-Diphosphonic Acid as a “Green Catalyst” - Panshina, S.Yu.; Bakibaev, A.A.; Guslyakov, A.N.; Malkov, V.S. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Glycoluril (2,4,6,8-tetraazabicyclo[3.3.0]octane-3,7-dione) and its derivatives have a special place in chemis-try of heterocyclic compounds. The macrocyclic derivatives of glycoluril, namely cucurbit[n]urils have re-cently attracted the greatest interest due to their unique properties. Cucurbit[n]urils are usually synthesized by the condensation reaction of glycoluril with paraformaldehyde using strong mineral acids as a catalyst. In this work, 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP) was used for the first time as a catalyst for “Green chemistry” in the synthesis of cucurbit[6]uril in an aqueous medium. The reaction of glycoluril and paraform-aldehyde in a ratio of 1: 2 with two equivalents of 1-hydroxyethylidene-1,1-diphosphonic acid as a catalyst was carried out, in which the hexamer of cucurbituril (n = 6) was obtained in 25 % yield. The clathrate of cu-curbit[6]uril with acetone was obtained by treating the cucurbituril hexamer with acetone. The reaction of glycoluril with paraformaldehyde in the presence of HEDP can be used as a competitive method for the syn-thesis of cucurbit[6]uril. The structures of the obtained compounds were proven by NMR and IR spectrosco-py methods. The phase composition of isolated crystals of cucurbit[6]uril hydrate was analyzed by the pow-der X-ray diffraction (XRD)
Кукурбит[6]урилдің синтезі 1-гидроксиэтан-1,1-дифосфон қышқылын «жасыл катализатор» ретінде пайдалану арқылы жүзеге асырылды
Синтез кукурбит[6]урила с использованием 1-гидроксиэтан-1,1-дифосфоновой кислоты в качестве «зеленого катализатора»
Keywords: cucurbit[6]uril; 1-hydroxyethylidene-1; 1-diphosphonic acid; glycoluril; paraformaldehyde; NMR; “Green” catalyst; oligomer; “guest-host” interactions